1992
DOI: 10.1021/jm00090a013
|View full text |Cite
|
Sign up to set email alerts
|

Iodoaminopotentidine and related compounds: a new class of ligands with high affinity and selectivity for the histamine H2 receptor

Abstract: The synthesis and biological evaluation of a new class of histamine H2 antagonists with N-cyano-N'-[omega-[3-(1-piperidinylmethyl)phenoxy] alkyl]guanidine partial structure are described as part of an extensive research program to find model compounds for the development of new radioligands with high H2 affinity and specific activity. High receptor affinity is achieved by an additional (substituted) aromatic ring, which is connected with the third guanidine N by a carbon chain spacer and an amine, carboxamide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 4 publications
(7 reference statements)
5
70
1
Order By: Relevance
“…However, neither APT nor I-APT modified the acid secretion induced by forskolin (which acts at intracellular sites beyond the H2 receptor) and the inotropic response to adrenaline in the papillary muscle, indicating that both compounds are selective for H2 receptors at concentrations that depressed the maximal response to histamine. Indeed, other studies have previously shown that these compounds are highly selective for H2 receptors and ['251l-APT has been considered the most valuable probe for labelling H2 receptors in different tissues (Ruat et al, 1990;Hirschfeld et al, 1992). Receptor-protection experiments in the present study showed that the co-administration of the surmountable antagonist ranitidine was capable of restoring the maximal response to histamine after APT, suggesting that APT and ranitidine interact with a common binding site.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, neither APT nor I-APT modified the acid secretion induced by forskolin (which acts at intracellular sites beyond the H2 receptor) and the inotropic response to adrenaline in the papillary muscle, indicating that both compounds are selective for H2 receptors at concentrations that depressed the maximal response to histamine. Indeed, other studies have previously shown that these compounds are highly selective for H2 receptors and ['251l-APT has been considered the most valuable probe for labelling H2 receptors in different tissues (Ruat et al, 1990;Hirschfeld et al, 1992). Receptor-protection experiments in the present study showed that the co-administration of the surmountable antagonist ranitidine was capable of restoring the maximal response to histamine after APT, suggesting that APT and ranitidine interact with a common binding site.…”
Section: Discussionsupporting
confidence: 61%
“…Those compounds with more lipophilic structural components expressed significantly lower pD2 values in the papillary muscle (Buschauer, 1989). Radioligand binding studies in guinea-pig cerebral membranes revealed that APT and I-APT have high affinity for H2 receptors (pK =8.01 and 9.15, respectively), being significantly more potent in binding assays than in functional experiments (guinea-pig atrium); this presumably reflects an easier access of these compounds to the H2 receptors in membrane preparations rather than an H2 receptor heterogeneity (Hirschfeld et al, 1992). Several different mechanisms can account for the insurmountable antagonism produced by APT and I-APT in heart and stomach: non-specific effects involving sites other than H2 receptors, allosteric interaction, irreversible or slowly reversible antagonism.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ARP and BU-E-43 were synthesized as described previously (Buschauer, 1989). APT and IAPT were prepared as described previously (Hirschfeld et al, 1992). Suprahistaprodifen was synthesized as described previously (Elz et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…In the rat, Northern hybridization analysis has revealed high expression in various parts of the brain, including cerebral cortex, striatum, hippocampus, and hypothalamus. The highest mRNA expression in the rat brain was seen in brain stem Hirschfeld et al, 1992), where several other methods have suggested important physiologic actions. In another quantitative study, the expression in the stomach was reported to be 10-fold higher than that of several brain regions .…”
Section: Anatomic Frameworkmentioning
confidence: 97%